PKM Peningkatan Kemampuan Operasi Kalibatakur Dalam Bimbingan Olimpiade Matematika Di SD Negeri 3 Buluagung - Barep Yohanes; Isti Dwi Setyowati (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2022)
This article is based on Community Service (PKM) activities carried out at SD Negeri 3 Buluagung. The problems experienced by partners include students' understanding of the Kalibatakur (addition, subtraction, multiplication, and division) operation which is very lacking, minimal preparation if they have to send students to attend math olympiads, and do not have a math olympiad coaching team. The solution offered refers to the first problem in the form of increasing the operational ability of Kalibatakur students of SD Negeri 3 Buluagung. The output that has been obtained is in the form of a coaching method using drill questions Kalibatakur from easy questions and gradually more difficult ones. Coaching must be done regularly and continuously. A pleasant atmosphere should be felt by students during the training.